Numerical Investigation of A New Junctionless Phototransistor for High-Performance and Ultra-Low Power Infrared Communication Applications - H. Ferhati; Faycal Djeffal; T. Bentercia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
In this paper, a new junctionless optical controlled field effect transistor (JL-OCFET) is proposed to improve the device performance as well as achieving low power consumption. An overall optical and electrical performances comparison of the proposed junctionless design and the conventional inversion mode structure (IM-OCFET) has been developed numerically, to assess the optical modulation behavior of the OCFET for low power optical interconnections applications. It is found that, the proposed design demonstrates excellent capability in decreasing the phototransistor power consumption for inter-chip optical communication application. Moreover, the proposed device offers superior sensitivity and ION/IOFF ratio, in addition to lower signal to noise ratio as compared to the conventional IM-OCFET structure. The obtained results indicate the crucial role of the junctionless (JL) design in enhancing the phototransistor performance and reducing the total power dissipation. Such a very sensitive OCFET can be very promising in the future low power optical receiver less compatible to CMOS modern technology for high-quality inter-chips data communication applications.